Correction to: Health effects of milder winters: a review of evidence from the United Kingdom - Shakoor Hajat (BMC, 2018)
Correction After publication of the article [1], it has been brought to our attention that there is an error in the abstract. The line that reads "a 1 °C fall during winter months led to reductions of 4.5%, 3.9% and 11.2%" should say "a 1 °C fall during winter months led to increases of 4.5%, 3.9% and 11.2%".